A trial of clenbuterol in bronchial asthma. Issue 6 (December 1977) - Anderson, G; Wilkins, E
Abstract : Clenbuterol is a beta 2-sympathomimetic bronchodilator. In a double-blind cross-over trial in 19 asthmatic patients with reversible airways obstruction, oral administration of both clenbuterol (40 microgram) and salbutamol (4 mg) caused significantly greater increased in peak expiratory flow rate (PEFR) than placebo, that of clenbuterol lasting longer. The patients' subjective assessment also suggested the relief of their symptoms by the active drugs. Side-effects were minimal.